Insights Biol Med 2017
DOI: 10.29328/journal.hjbm.1001003
|View full text |Cite
|
Sign up to set email alerts
|

Fungi present in home and their impact on human health-A short review

Abstract: It is estimated that even up to 30% of buildings worldwide may be the subject of complaints connected with the quality of indoor air. Potential sources of air pollution can be both organic and inorganic particles. This article focuses on biological air pollutants from living and dead biological sources, especially those connected with fungi. Fungi found in the indoor air of domestic dwellings in a large extent are similar in their species composition to those found on the outside of the building. Microorganism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…However, it is known that viable and dead fungal spores and mycelial fragments may induce exacerbations of allergies and other inflammation reactions, which are seen at high concentrations of Alternaria , Cladosporium , Aspergillus , Penicillium , or Trichoderma genus as well as order Mucorales . 67 Recent study showed that in macrophages derived from human THP‐1 monocytes, STC and enniatin B applied alone induced a modest inflammatory response but in the presence of fungal cell wall β‐glucan provoked synergistically increased expression several inflammation‐related genes, mitochondrial damage, and autophagocytosis 68 . Taking into account the fungal dust metabolite profile and mycobiota composition of damp indoors in the present study, we may only speculate on the synergistic interactions of these complex mixtures and influence on human health.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is known that viable and dead fungal spores and mycelial fragments may induce exacerbations of allergies and other inflammation reactions, which are seen at high concentrations of Alternaria , Cladosporium , Aspergillus , Penicillium , or Trichoderma genus as well as order Mucorales . 67 Recent study showed that in macrophages derived from human THP‐1 monocytes, STC and enniatin B applied alone induced a modest inflammatory response but in the presence of fungal cell wall β‐glucan provoked synergistically increased expression several inflammation‐related genes, mitochondrial damage, and autophagocytosis 68 . Taking into account the fungal dust metabolite profile and mycobiota composition of damp indoors in the present study, we may only speculate on the synergistic interactions of these complex mixtures and influence on human health.…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms that have reached the interior of the rooms will be deposited on damp walls, at the level of windows, carpets or in any other areas with a high degree of humidity. Spores or conidia and other structures of fungi enter the human body in different ways: nasal, skin [73]. The periodic study of the microflora of the air is necessary because the risk of biodeterioration and human illness increases proportionally with the number of pathogenic germs and with the presence of certain pathogenic or potentially pathogenic species and with the presence of favorable conditions for their development (humidity, temperature, certain material types from which objects are made).…”
Section: Degree Of Fungal Contaminationmentioning
confidence: 99%
“…Exposure and sensitization to fungal allergens can promote the development and worsening of allergic diseases. Allergic manifestations induced by fungi are recognized and include asthma, rhinitis, conjunctivitis, allergic sinusitis, pneumonia, urticaria, atopic dermatitis [52,73]. Allergic reactions can occur through all four types of hypersensitivity reactions I-IV.…”
Section: Degree Of Fungal Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, microscopic fungi may be a contributing factor to sick building syndrome. Further toxic and carcinogenic effects of these substances remain a question [7,8]. Some fungal species may occasionally cause human diseases, for example, diseases of the skin, eye cornea, or inflammation of the internal organs.…”
Section: Introductionmentioning
confidence: 99%